Determinan yang mempengaruhi kualitas laba pada perusahaan manufaktur di indonesia (analisis sebelum dan sesudah adopsi ifrs) - Agus Khazin Fauzi; Endar Pituringsih; Biana Adha Inapty ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2015)
This research is aimed at examining and analyzing the effect of investment opportunity set (IOS), liquidity, leverage and accounting conservatism on the quality of profit at manufacturing company before and after the adoption of IFRS. This research was classified as associative research. The samples used are 52 manufacturing companies registred at Indonesian Stock Exchange during the period of 2008-2013. The analysis employed multiple linear regression and paired sample t-test. The research showed that IOS variable and liquidity do not significantly affect on the quality of profit before and after the adoption of IFRS. While, leverage variable does not significantly affect the quality of profit before the adoption, but it does significantly after the adoption. Then, accounting conservatism variable had significantly affect on the quality of profit before and after the adoption of IFRS. The paired sample t-test showed that there is difference in quality of profit, liquidity, and accounting conservatism before and after the adoption of IFRS. While this research showed that IOS and leverage are different either before or after the adoption of IFRS.Keywords : quality of profit, investment opportunity set (IOS), liquidity, leverage and acounting conservatism.